Perspektif Berpikir Rasional, Berpikir Kritis, dan Kecerdasan dalam Pembelajaran : Sebuah Review - Witjati, Lilih; Latipah, Eva (FKIP Unirow Tuban, 2024)
This study aims to provide information about the perspectives of rational thinking, critical thinking and intelligence in learning which is a study of the book Innovations in Educational Psychology: Perspectives on Learning, Teaching, and Human Development by Robert J. Sternberg, PhD and David D. Preiss, PhD. . The method used in this research is library research. The data used in this study is secondary data in the form of research results such as books, scientific journals, research reports, and other relevant sources. The results showed that (1) critical thinking is an effort to evaluate the thinking process, the ability to evaluate evidence and arguments independently. (2) In critical thinking based on rationality. (3) in rational thinking there are requirements for cognitive capacity, reflective thinking and mindware. (4) in rational thinking there are instrumental rationale and epistemic rationale. (5) the characteristics of rational thinking include three things, namely reflective thinking, algorithmic thinking and autonomous thinking. (6) rationality is a more comprehensive construction than intelligence. Likewise, the construct of critical thinking is included in the construct of rationality.